Rola gospodarki leśnej w rozwoju obszarów wiejskich w Polsce - Szramka, Hubert (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The possibility of agriculture and forestry co-operation regarding the development of rural areas of Poland was introduced by the author in his work. The first part presents the process of ecological changes in forestry and making thee effort to implement these changes in agriculture. The second part shows the actions taken by the State Forests regarding the promotion of versatile and balanced forest economy. The emphasis is also put on the influence of the actions taken regarding the development of rural areas, especially pertaining to the creation of new work places. The author points to the importance of the afforestations in raising the value for the tourism and rural recreation areas as well. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 137-141